Комплексна оцінка показників імунного статусу, прооксидантної та антиоксидантної систем у хворих на дифузний токсичний зоб за умов йододефіциту - Пасєчко, Н. В.; Свистун, І. І.; Швед, Л. В. (Clinical Endocrinology and Endocrine Surgery, 2008)
The results of examination of 30 patients with diffuse toxic goiter were represented (among them there were 8 patients with thyreotoxicosis of moderate severity and 22 with the hard one). All the patients were examined in antioxidant system activities, lipid peroxidation and immune system state. The activation of lipid peroxidation, increase of endogen intoxication level and decrease of antioxidant system's activity were revealed. The degree of these changes depends on the severity of thyreotoxicosis. Patients with diffuse toxic goiter had T-lymphocytes disorder — decrease of their general level, T-helpers and T-suppressors. Besides, the activation of antibodies formation with increasing amount of circulated immune complexes was noted. The increased level of ceruloplasmin might suggest significant catabolic process with increased level of cells.